Determinan audit report lag pada seluruh perusahaan terdaftar di BEI tahun 2020 - Leonita, Eka Denistia; Triani, Ni Nyoman Alit (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aim to obtain empirical evidence regarding the factors that can affect the delay in submitting audited financial reports (audit report lag) for all companies that listed on Bursa Efek Indonesia in 2020. This study used a quantitative method. The type of data used is secondary data from the company's financial statements and annual reports. The sample in this study was taken from data from all companies in various sectors listed on the IDX. The data analysis technique in this study used multiple linear regression test. The results of this study stated that the variables of liquidity, audit fees, and subsidiaries have an effect on audit report lag, while audit firm size, company size, and solvability variables have no effect on audit report lag.